DEVELOPING STUDENTS' ENTREPRENEURIAL SPIRIT THROUGH THE SUBJECT ILMU HITUNG KEUANGAN - Subekti, Retno (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
This article was written to share the experiences of teaching 'trading or doing business' in the subject of Ilmu Hitung Keuangan in 2010. This Article also share about the phenomenon of appeared "˜kantin kejujuran' or the honesty canteen in Mathematics and Natural Sciences Faculty of Yogyakarta State University in early 2011. Based on the syllabus of the subject, there is a topic of trading that makes lecturer is motivated to participate in developing the entrepreneurial spirit of students. The way taken by the lecturer was giving big trust to the students to manage funds for trading. Before trading begins, students should discuss about what are the things that can be bought cheaply and then sold with ease so that will give them the advantage. The result is that all groups got benefit. 4 groups formed are the group of "˜donuts', "˜accessories', "˜snacks', and "˜stickers'. Then groups of food division that are donuts group and snack's one were part of the pioneers of honesty canteen. This method is in line with lecturers expectancy to participate and develop entrepreneurship on campus.